PEMBUDAYAAN NILAI-NILAI ISLAMI DALAM MEMBANGUN KARAKTER BANGSA (Studi Kasus di Sekolah Menengah KejuruanNegeri 1 Cimahi) - Yudi Kuswandi; Emma Himayaturrohmah (Tatar Pasundan : Jurnal Diklat Keagamaan, 2018)
The purpose of this article is to describe the process of civilizing Islamic values in educational activities in the formal education environment. In theory, formal education institutions are considered effective in cultivating Islamic values for character building for learning citizens. Professional practitioner activities combine constellations of values, goals, sanctions, knowledge and methods that are consistently manifested in the form of certain moral ideas. The operational forms as are expressed in everyday actions with a specified level of system and target. The study was carried out through observation and interviews with purposive participants and also snowballing method. All available information is analyzed qualitatively. The results of this study state that the civilizing of character values in formal education institutions becomes effective because psychologically students will be more obedient, fearful, and reluctant to teachers than parents or the general public. The main key is consistent in the application of rules, evaluation, reward and punishment in applying religious character, moderate, intelligent, independent and nationality which is a benchmark for the successful planting of Islamic values to shape the nation's character.  Key words: Civilization, Education, Islamic Values, Character of the Nation.